Clinician and manager perceptions of factors leading to ward patient clinical deterioration. Issue 6 (November 2018) - Allen, Joshua; Jones, Daryl; Currey, Judy
Abstract: Background: Improving the timely recognition and response to clinical deterioration is a critical challenge for clinicians, educators, administrators and researchers. Clinical deterioration leading to Rapid Response Team review is associated with poor patient outcomes. A range of factors associated with clinical deterioration and its outcomes have been identified, and may help with early identification of deteriorating patients. However, the relative importance of each factor on the development of clinical deterioration is unknown. Objective: To identify the relative importance of factors contributing to the development of clinical deterioration in ward patients, as perceived by health professionals who have experience in recognising or responding to clinical deterioration, or in the management, administration or governance of RRSs. Methods: A written questionnaire containing 12 pre-determined factors was provided to participants. Participants were asked to rank the items from most to least important contributors to ward patient deterioration. The study took place during a session of the Australia and New Zealand Intensive Care Society Rapid Response Team conference. Results: A final sample of 233 (83% response rate), returned the questionnaire. The sample comprised specialist ICU registered nurses with direct patient contact (64%), ICU consultant doctors (17%), ICU nurse managers (7%), hospital administrators (2%), ICU registrars (2%), quality coordinators (2%) and non-hospital staff (4%). The patient's presenting illness/main diagnosis was the highest ranked factor, followed by pre-existing co-morbidities, seniority of nursing ward staff, medical documentation, senior medical staff, and interdisciplinary communication. Almost two-thirds of participants ranked patient characteristics as the most important contributor to clinical deterioration. Conclusion: Health professionals who have experience in recognising or responding to clinical deterioration, or in the management, administration or governance of RRSs perceive that patient characteristics such as the patient's primary diagnosis and comorbidities to be the most important contributors to clinical deterioration.